2021
DOI: 10.1039/d1fo01542g
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method based on an inhibitor–enzyme complex to screen an active compound against lipase from Toona sinensis

Abstract: As a popular vegetable, Toona sinensis has a wide range of bioactivities including lipase inhibitory activity. In the present study, an efficient and rapid method using ligand-enzyme complex was established...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The in vitro activity assay revealed that the butterfly pea flower (CT) extract inhibits lipase with an IC50 value of 131.7867 ± 5.27 ppm. This value was lower than that for the in vitro activity test of Toona sinensis, with an IC50 value of 118.8 ± 1.53 µg/mL [28], and for the methanolic extract of Hibiscus sabdariffa L. (Malvaceae), with an IC50 value of 35.8 ± 0.8 µg/mL, yet it was higher than the IC 50 value of 152.0 ± 7.0 µg/mL for the methanolic extract of Tamarindus indica L. (Leguminosae) [30].…”
Section: Antihyperlipidemic Activitycontrasting
confidence: 58%
See 1 more Smart Citation
“…The in vitro activity assay revealed that the butterfly pea flower (CT) extract inhibits lipase with an IC50 value of 131.7867 ± 5.27 ppm. This value was lower than that for the in vitro activity test of Toona sinensis, with an IC50 value of 118.8 ± 1.53 µg/mL [28], and for the methanolic extract of Hibiscus sabdariffa L. (Malvaceae), with an IC50 value of 35.8 ± 0.8 µg/mL, yet it was higher than the IC 50 value of 152.0 ± 7.0 µg/mL for the methanolic extract of Tamarindus indica L. (Leguminosae) [30].…”
Section: Antihyperlipidemic Activitycontrasting
confidence: 58%
“…The lipase inhibition test method uses ρ-NPB, which acts as a substrate, with the addition of a lipase catalyst to produce butyrate products and ρ-nitrophenolate ions with a yellow color [28]. The antilipase activity test was carried out according to the results of optimization: 30 min of incubation time, 3 mg/mL substrate concentration, and 0.025 mg/mL enzyme concentration.…”
Section: Antihyperlipidemic Activitymentioning
confidence: 99%
“…In this study, the exposure of chronic stress caused depletion of monoamine hormones; however, EFCS increased the levels of dopamine, tryptophan, 5-HT, and melatonin ( Figure 6 ). It has been reported that Cedrela sinensis leaf is rich in hormonal precursor amino acids, such as tryptophan, tyrosine, and glutamic acid, that are associated with stress reduction [ 74 , 75 ]. These amino acids are absorbed into the body and converted to serotonin, melatonin, dopamine, and γ-aminobutyric acid (GABA), and they suppress stress and help to suppress the imbalance of the HPA axis [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory kinetics of puerarin, daidzin, and daidzein against α -glucosidase was tested based on the reported enzyme activity determination method. 11 First, in the presence of inhibitors, different concentrations of α -glucosidase were reacted with the same concentration of p -NPG. Subsequently, the amount of p -NPG was changed, while the amount of α -glucosidase remained unchanged.…”
Section: Methodsmentioning
confidence: 99%